DIFFERENCES IN THE ANTHROPOLOGICAL PROFILE OF THE BASKETBALL REFEREES WITH REGARDS TO THEIR CHRONOLOGICAL AGE - Saša Baščevan; Damir Knjaz; Bojan Matković; Tomislav Rupčić; Saša Rodić (University of Banja Luka, Faculty of physical education and sport, 2011)
The aim of our research was to determine differences in the anthropological profile of best Croatian basketball referees with regard to their chronological age. The study included 31 referees from the A referee list in the competitive season 2008/2009. In order to determine the statistical differences they were divided into two age groups; young (n = 16) including referees age 26-32 and older group (n = 15) including referees aged 33-46. Participants were tested on different variables for the assessment of motor and functional abilities and morphological characteristics. Also, in this research were included two variables called Quality of officiating and Experience. Data analysis was performed using the software package STATISTICA for Windows, 8th version. For each variable basic descriptive statistical parameter was calculated. Analysis of statistical differences in the anthro-pological profile with regard to the chronological age of basketball referees was performed using t-test for independent samples. According to our results basketball referees differ only in the vari-ables for the assessment of motor abilities, while there were no statistically significant differences in the tested morphological characteristics and functional abilities regarding referees' age. To conclude, investigated basketball referees were all well physically prepared, meeting high standards of physical conditioning-motor preparation needed for the basketball games of the highest national level.